Selected defects of long-operated vitrified clay sewer pipes - Kuliczkowska, Emilia; Wijas, Katarzyna (Instal, 2022)
The aim of the article is to compare the size and frequency of selected line and point defects observed in long operated vitrified clay sewer pipes during their CCTV inspection carried out in the years 1991 – 2000 and 2003 – 2017. The analysis concerns the following defects: solid sediment, longitudinal scratches and cracks, roots growing into the sewer and losses of fragments of the structure coating. The causes and consequences of the occurrence of these defects are listed, as well as a description of the method for their assessment. Similarities and differences in the occurrence and size of the analyzed defects were indicated.